A guarda municipal de Belo Horizonte no processo de descentralização da política de segurança pública para os municípios brasileiros - Silva, Laura Angélica Moreira (2012)
Having the backdrop of the debate about the Brazilian federalism, this paper discuss the conformation and activity of the Municipal Guards in the country, in terms the public security policy proposed by the Union, and in specific character as the Municipal Guard of Belo Horizonte falls in this debate. The hypothesis that guides this it's that the provision of security, through the Municipal Guards, both nationally and in Belo Horizonte, is not an uniform action and mainly depends on the will of the local Executive and demands present in each municipality. The theoretical framework of this paper discusses federalism, decentralization, public security policy and Municipal Guards. As a method to achieve this goal, besides the literature review was conducted structured interviews with the managers and municipal guards who work in the Guard of Belo Horizonte and used secondary data to i) analyze the dispersion of the regions of the Municipal Guards federation and also by population, in order to characterize and analyze the training received, type of weapon used and the training commander and ii) analyze the interventions by the Municipal Guard of Belo Horizonte. The conclusion is that, even with positive and negative incentives proposed by the Union, the role of the Municipal Guard is quite discontinuous and heterogeneous in the country depending on the initiative of the mayor to institute and proceedwith this security policy at the municipal level. The Guard of Belo Horizonte follows the national scene and has a secondary role due to the absence of a demand itself, acting on the basis of a partnership mainly with the Military Police of Minas Gerais, in preventive, within the municipal services.